The Constraints on valuing local products in the oasis systems: (The palm fruit production in oases of the Middle Daraa as a model) - Rachidi, Moulay Hfid; Bouzid, Naciba; Bouhamed, Ahmed (Journal of Humanities & Social Sciences, 2022)
Palm trees are considered the most important component of the ecosystem in the oasis, and the cornerstone of its economy. They also play an essential role in protecting from desertification creeping in addition to their contribution to the creation of a local climate that preserves the other types of vegetation and agriculture. This article treats problematic questions related to the valuation of dates in the ecosystem of oases given the salient role of those trees. The study attempted to monitor the potentials of the oases in the Middle Daraa in terms of the variety of dates’ species, the extent of the oasis field, in addition to the local farmers’ skills in dealing with dates and the interventions of the actors in the valuation of dates as it is one of the main goals of the green Morocco plan. The study has concluded that the fragility of the natural environment, the weakness of the actors interventions and their lack of effectiveness in overcoming the structural imbalances facing the dates sector, is constituting the most important constraints facing the process of valuing dates in the middle Daraa , as a result of dealing with the oasis system with an approach that did not take into consideration the peculiarities of this fragile field, especially the coercion to manage the scarcity of water resources and the small size of the exploitations.